Evaluation of the Removal of Hydrocarbons from Soil Media Using Persulfate Oxidation in the Presence of Mineral Siderite - Farzad Mohammadi; Mahmood Alimohammadi; Amir Hossein Mahvi; Shahrokh Nazmara; Sajad Mazloomi; Masoomeh Askari (Mazandaran University of Medical Sciences, 2016)
Introduction and purpose: Soil contamination by petroleum is mostly resulted from oil exploration, refining processes, leaking of oil products from storage tanks, leaking from pipelines due to pipe friction and decay, refinery wastewater discharge and agricultural irrigation with such materials. Sodium persulfate (Na2S2O8), which is a chemical oxidant, could be activated in the presence of ferrous (Fe2+) and, leading to the treatment of a wide range of soil contaminants. Therefore, this study aimed to evaluate the removal of hydrocarbons from soil media using persulfate oxidation in the presence of mineral siderite. Methods: Initially, oil-contaminated soil was prepared in the form of two separate samples, including silt-clay and sandy-loam soils, which were orderly spiked with 5000 mg fuel oil per kilogram of dry soil. Following that, the effects of various factors, such as different concentrations of persulfate (100-500 mmol/L) and siderite (0.1-0.5 g/L), pH (3-9) and temperature (20-60◦C) and the removal of petroleum hydrocarbon were assessed.Results: In this study, the optimum condition for degeneration of total petroleum hydrocarbon in silt-clay soils was reported, as follows: temperature: 60◦C, pH: 3, and persulfate/siderite molar ratio of 400 mmol/L to 4.0 g/L. Meanwhile, the optimum condition for the removal of hydrocarbon from sandy-loam soils was pH: 3, temperature: 60◦C and persulfate/siderite molar ratio of 300 mmol/L to 3.0 g/L.Conclusion: According to the results of this study, the optimal amount of persulfate and siderite could be used to remove hydrocarbons from contaminated soils.